(untitled) (Scientific journal of the Fergana State University, 2026)
This article explores the linguistic characteristics and developments of the Middle Ages, focusing on the evolution of Middle English and its relationship with other languages of the time. It examines the rise of vernacular languages in medieval Europe, highlighting how Latin, French, and local dialects coexisted and influenced each other. Key topics include the transition from Old English to Middle English, the Great Vowel Shift, and the significant role of multilingualism, oral traditions, and religious texts. Through analysis of primary texts and historical linguistic evidence, this study provides a comprehensive overview of the linguistic landscape of the Middle Ages, emphasizing the dynamic interplay between language, culture, and history.